2019
DOI: 10.1101/516906
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Control of Staphylococcus aureus quorum sensing by a membrane-embedded peptidase

Abstract: 26Gram-positive bacteria process and release small peptides or "pheromones" that act as signals 27 for the induction of adaptive traits including those involved in pathogenesis. One class of small 28 signaling pheromones is the cyclic auto-inducing peptides (AIPs), which regulate expression of 29 genes that orchestrate virulence and persistence in a range of microbes including 30Staphylococci, Listeria, Clostridia, and Enterococci. In a genetic screen for Staphylococcus 31 aureus secreted virulence factors, we… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 96 publications
(122 reference statements)
1
10
0
Order By: Relevance
“…Relatedly, the protein product of SAUSA300_1984 ( mroQ ) acts within the Agr pathway. 43 Moreover, the protein product of SAUSA300_1467 ( lpdA ) has been shown to have a role in branched-chain fatty acid biosynthesis. 44 The selected transposants were also tested for labeling with a second fluorescent probe ( DBCO-AF488 ) in order to determine the role of the fluorophore in PG labeling ( Figure S4 ).…”
Section: Resultsmentioning
confidence: 99%
“…Relatedly, the protein product of SAUSA300_1984 ( mroQ ) acts within the Agr pathway. 43 Moreover, the protein product of SAUSA300_1467 ( lpdA ) has been shown to have a role in branched-chain fatty acid biosynthesis. 44 The selected transposants were also tested for labeling with a second fluorescent probe ( DBCO-AF488 ) in order to determine the role of the fluorophore in PG labeling ( Figure S4 ).…”
Section: Resultsmentioning
confidence: 99%
“…Agr is a quorum-sensing operon that is also an important regulatory factor that controls virulence factors, including toxin production, mecA expression, and biofilm formation of MRSA [10,22,24,[51][52][53]. Thus, it is extensively studied as a target for controlling MRSA [52][53][54]. However, recent studies suggested a more complex role of Agr and it showed quite strain dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…The possible mechanism involves hydrolysis of auto‐inducing peptide by mroQ coding synthase, resulting in the inactivation of agrC . This subsequently inactivated the function of downstream RNAII and RNAIII, and the regulated genes, including coagulase, showed no expression 23,24 …”
Section: Discussionmentioning
confidence: 99%